2011
DOI: 10.1177/0748233710389851
|View full text |Cite
|
Sign up to set email alerts
|

Testicular apoptosis and histopathological changes induced by a 2.45 GHz electromagnetic field

Abstract: There is a growing public concern about the potential human health hazard caused by exposure to electromagnetic radiation (EMR). The objective of this study is to investigate the effects of 2450 mhz electromagnetic field on apoptosis and histopathological changes on rat testis tissue. Twelve-week-old male Wistar Albino rats were used in this study. Eighteen rats equally divided into three different groups which were named group I, II and III. Cage control (group I), sham control (group II) and 2.45 GHz EMR (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 32 publications
3
47
1
4
Order By: Relevance
“…Our previous study showed that magnetic radiation was induced by 2.45 GHz electromagnetic radiation causing testicular apoptosis (7). Occurrence of Bax gene and caspase-3 and -8 enzymes demonstrated that electromagnetic radiation might trigger apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study showed that magnetic radiation was induced by 2.45 GHz electromagnetic radiation causing testicular apoptosis (7). Occurrence of Bax gene and caspase-3 and -8 enzymes demonstrated that electromagnetic radiation might trigger apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The whole system performance of the exposure device was tested and checked in the Laboratory of the Department of Electronics and Communication Engineering (Suleyman Demirel University, Isparta, Turkey). Exposure design and methodology were adapted from a similar study (7,22,23). All six rats in the groups were exposed at the same time in the exposure system.…”
Section: Exposure System and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In 28-day-old rats, reduced spermatogenesis has been observed after repeated exposure to 0.9 or 2.45 GHz radiation, together with decreased numbers of Leydig cells and increased oxidative stress and apoptosis in testicular tissue [26,27]. Once more, however, the available information is contradictory, no morphological or biochemical indications of increased apoptosis [5,28] or of pre-apoptotic states with increased caspase activity [29,30] having been observed in male sexual cells in other studies after exposure of animals to single or combined radio frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the exposure system have been described in detail elsewhere (19,20). However, we reduced the power values to 1 mW/m2 in the experiments as described below.…”
Section: Exposure System and Designmentioning
confidence: 99%